(untitled) (Global Journal of Science Frontier Research, 2024)
Efficient utilization of available resources is a promising research direction. In-depth studies can provide a unique platform for reducing fuel consumption while simultaneously reducing pollution, thereby avoiding environmental pollution and health hazards for this purpose various fuel addictive are being used now. A laser additive for liquid and gaseous fuel is yet to be developed. In this context, we successfully used the 2-6 mid-infrared spectrum as a fuel additive. To generate mid-infrared we invented a hand-lit pocket-size mid-infrared generating automizer (MIRGA). The trial fuels were irradiated with this spectral range, which caused chemical changes in the fuels.